2012
DOI: 10.1177/0194599812465059
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for the Treatment of Sialorrhea

Abstract: Botulinum toxin is a clinically effective therapy that improves drooling severity in patients with sialorrhea. Future studies will need to further evaluate the technique and examine dosages required to achieve optimal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 26 publications
(47 reference statements)
3
41
1
4
Order By: Relevance
“…A recent meta‐analysis from eight randomized placebo‐controlled trials of BTX injection in other diseases showed that common side effects included increased saliva thickness (3.9%), dysphagia (3.3%), xerostomia (3.3%), and pneumonia (2.2%) 21. Although our patients did not experience any adverse reaction related to BTXA, dysphagia could not be evaluated due to tube feeding resulting from decreased mentality.…”
Section: Discussionmentioning
confidence: 73%
“…A recent meta‐analysis from eight randomized placebo‐controlled trials of BTX injection in other diseases showed that common side effects included increased saliva thickness (3.9%), dysphagia (3.3%), xerostomia (3.3%), and pneumonia (2.2%) 21. Although our patients did not experience any adverse reaction related to BTXA, dysphagia could not be evaluated due to tube feeding resulting from decreased mentality.…”
Section: Discussionmentioning
confidence: 73%
“…10,13 When injected into the salivary gland, it blocks the release of acetylcholine at the cholinergic neurosecretory junction 13,29. Reinnervation occurs over several months as new neuroglandular junctions are created 3…”
Section: Management Optionsmentioning
confidence: 99%
“…Another systematic review included four RCTs in children (all included in the other two reviews), involving a total of 103 children 10. The review reported a significant improvement in drooling severity in children at 4 weeks (standardised mean difference –1.84, 95% CI –2.67 to –1.00) 10.…”
Section: Management Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…aufrechterhalten werden. Im aktuellen interdisziplinären Konsensus hat sich die Injektion von Botulinumtoxin in die Kopfspeicheldrüsen etabliert [1,2] 11 Behandlungen darunter. In der Gesamtbetrachtung aller 117 Behandlungen lag der Anteil mit "gut" ("gut" sowie "gerne mehr") bewertetem Therapieansprechen in der Standarddosis bei 51 % (90 %), in der niedriger dosierten Gruppe bei 65 % (88 %) und in der höher dosierten Gruppe bei 73 % (95 %).…”
unclassified